Liquidity constraints, household wealth, and entrepreneurship revisited - Robert W. Fairlie; Harry A. Krashinsky (Institute for the Study of Labor (IZA), 2006)
Hurst and Lusardi (2004) recently challenged the long-standing belief that liquidity constraints are important causal determinants of entry into self-employment. They demonstrate that the oft-cited positive relationship between entry rates and assets is actually unchanging as assets increase from the 1st to the 95th percentile of the asset distribution, but rise drastically after this point. They also apply a new instrument, changes in house prices, for wealth in the entry equation, and show that instrumented wealth is not a significant determinant of entry. We reinterpret these findings: first, we demonstrate that bifurcating the sample into workers who enter self-employment after job loss and those who do not reveals steadily increasing entry rates as assets increase in both subsamples. We argue that these two groups merit a separate analysis, because a careful examination of the entrepreneurial choice model of Evans and Jovanovic (1989) reveals that the two groups face different incentives, and thus have different solutions to the entrepreneurial decision. Second, we use microdata from matched Current Population Surveys (1993-2004) to demonstrate that housing appreciation measured at the MSA-level is a significantly positive determinant of entry into self-employment. Our estimates indicate that a 10 percent annual increase in housing equity increases the mean probability of entrepreneurship by roughly 20 percent and that the effect is not concentrated at the upper tail of the distribution.
Keywords: J23; 330; entrepreneurship; liquidity constraints; self-employment